FAKTOR PENENTU PERUSAHAAN MELAKUKAN PENGAMBILAN KEPUTUSAN HEDGING PADA DERIVATIF VALUTA ASING (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2014) - Prasetiono, Prasetiono; Hidayah, Na’imatul Hidayah (Faculty of Economics and Business Diponegoro University, 2016)
Import export activities requires companies to use foreign currency to make a sale and purchase of products, this causes the company likely to suffer risk of loss foreign currency exchange rates, to reduce the risk of losses incurred, the company needs hedging by using derivative instruments. This study’s purpose is to analyze the influence of Debt to Equity Ratio, Interest Coverage Ratio, Growth Opportunity, Firm Size, Current Ratio, Foreign Liability, Managerial Ownership, and Institutional Ownership on Hedging decision.The population in this research is manufacturing companies listed on Indonesia Stock Exchange 2011-2014 period. The number of sample are 82 companies by using purposive sampling method with the provision of the company that publishes full financial statements.this research used logistic regressions analysis technique, to determine the variables affect the probability of the use of derivative instruments as hedging activity decision. The variabels used in this study are the Debt to Equity Ratio, Interest Coverage Ratio, Growth Opportunity, Firm Size, Current Ratio, Foreign Liability, Managerial Ownership, and Institutional Ownership.The results logistic regression analysis showed that of the eight variables used in this study, the variable Debt to Equity Ratio, Interest Coverage Ratio, Growth Opportunity, Firm Size, Current Ratio and Institutional Ownership significantly influence the decision Hedging, while the variable Foreign Liability and Managerial Ownership not significant effect on Hedging decision. The ability of the variable Debt to Equity Ratio, Interest Coverage Ratio, Growth Opportunity, Firm Size, Current Ratio, Foreign Liability, Managerial Ownership, and Institutional Ownership in explaining the probability of the use of hedging derivatives at 32% and the rest is explained by other variables outside the model.